2012
DOI: 10.1038/jcbfm.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Importance of T Lymphocytes in Brain Injury, Immunodeficiency, and Recovery after Cerebral Ischemia

Abstract: Following an ischemic stroke, T lymphocytes become activated, infiltrate the brain, and appear to release cytokines and reactive oxygen species to contribute to early inflammation and brain injury. However, some subsets of T lymphocytes may be beneficial even in the early stages after a stroke, and recent evidence suggests that T lymphocytes can also contribute to the repair and regeneration of the brain at later stages. In the hours to days after stroke, T-lymphocyte numbers are then reduced in the blood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(142 citation statements)
references
References 136 publications
(236 reference statements)
4
132
0
6
Order By: Relevance
“…13,18 It has been assumed that the process of postischemic brain inflammation is facilitated by reperfusion but is limited in the absence of reperfusion. Our study has examined the profile of immune cell infiltration at early time points after pMCAO in mice, a model of human MCA infarction lacking cerebral reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,18 It has been assumed that the process of postischemic brain inflammation is facilitated by reperfusion but is limited in the absence of reperfusion. Our study has examined the profile of immune cell infiltration at early time points after pMCAO in mice, a model of human MCA infarction lacking cerebral reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Further, T lymphocytes are now understood to contribute to ischemic brain injury after reperfusion. 13,14 Thus, Rag1 À / À mice that are deficient in lymphocytes appear to be partially protected from severe histochemical and functional outcomes after cerebral ischemia and reperfusion due to the absence of T lymphocytes. 15 By contrast, other infiltrating cells such as regulatory B cells may act to limit severity of stroke outcome after transient cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Необходимое для функционального восстановления создание новой нейральной сети достигается за счет акти-вации нейрогенеза, нейропластичности, синап-тогенеза, ангиогенеза и глиогенеза. Предпола-гается, что Т-клетки, вовлеченные в иммунный ответ, участвуют в запуске и продвижении этих репаративных механизмов преимущественно за счет продукции нейротрофических и регуля-торных факторов [9]. Действительно, Т-клетки принимают участие в поддержании нейрогенеза в гипокампе [131].…”
Section: адаптивный иммунный ответunclassified
“…Several studies have seen that an attenuation of the inflammatory process could be a possible way to widen the therapeutic window after the acute event [8,11,12]. However, other studies pointed out that the inflammatory response is necessary in order, for example, to remove dead neurons and other brain cells in the ischaemic core, and promote astrocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that T-cells also have an impact on tissue damage [12][13][14][15][16][17][18][19][20]. Several studies have seen that an attenuation of the inflammatory process could be a possible way to widen the therapeutic window after the acute event [8,11,12].…”
Section: Introductionmentioning
confidence: 99%